Amalan penyediaan dan penulisan bahan siaran media di Malaysia : kajian analisis kandungan - Mohd Yahya Mohamed Ariffin,; Md. Sidin Ahmad Ishak, (2010)
Probably the most basic tool of public relations is the media release. The purpose of media release is to be used by editors or the media people in preparing editorial for publication. A well-prepared release is required in order for it to be useful. This paper analyses the content of 420 media releases received by two mass media organisations. These documents are listed in an inventory and from this inventory, 11 aspects are examined. The aspects include title, page number, language medium, writing style, category of sender, and type of sender. This study observes that while many releases follow the standard format, their writing and preparation in certain aspects need to be improved to be seen and used by media editors.